Book three: the danger : dive - Korman, Gordon; Copyright Paperback Collection (Library of Congress) (New York : Scholastic Inc., 2003)
Four kids discover treasure at the bottom of the sea and try to remove it from the sunken ship it's in.
"An Apple paperback."
G5
Keywords: Shipwrecks -- Caribbean Area -- Fiction; Buried treasure -- Fiction; Shipwrecks -- Caribbean Area -- Juvenile fiction; Treasure troves -- Juvenile fiction; Caribbean Area -- Fiction; Caribbean Area -- Juvenile fiction; Adventure fiction; Children's stories